ChemInform Abstract: Palladium‐Catalyzed 1, 1‐Difunctionalization of Ethylene. Issue 1 (3rd January 2013) - Saini, Vaneet; Sigman, Matthew S.
Abstract The title reaction proceeds with aryl/vinyl/heteroaryl transmetalating agents and vinyl electrophiles under low pressure of ethylene and with a high regioselectivity.